FACTOR ANALYSIS OF STUDENT’S SATISFACTION ON ACADEMIC COURSES AT UNIVERSITAS ADVENT INDONESIA - Franklin Hutabarat; Reymand Hutabarat (Program Studi Magister Manajemen Universitas Advent Indonesia, 2018)
This study aims to identify factor the affecting student satisfaction in the Southern Asia Pacific Division Higher Education Institutions. Understanding these factors could help leaders in educational institutions to better plan their strategies and further research on student satisfaction. A set of questionnaire was developed and will be distributed to students at a higher education institution (HEI) institutions in Southern Asia Pacific Division Higher Education Institution namely Universitas Advent Indonesia (UNAI) of Indonesia